Analysis of the Rights and Obligations of Husband and Wife in the Compilation of Islamic Law: A Review from the Perspective of Gender Equality - Okti Nur Hidayah; Musyafangah; Ahmad Rezy Meidina (Legitima : Jurnal Hukum Keluarga Islam, 2023)
Purpose – This research aims to identify the manifestation of gender injustice in the Compilation of Islamic Law, especially in the chapter on the rights and obligations of husband and wife. Methods – The research method used is library research with qualitative analysis. Findings – The analysis shows that Article 79 Paragraph 1 creates stereotypical gender roles by reinforcing the traditional roles of husband and wife. On the other hand, Article 79 Clause 2, and Clause 3 reflect the principles of gender equality and justice in legal rights. The husband's duties, as set out in Article 80, involve a guiding role and financial responsibility, with the issue of discrimination in women's education in Article 80 Clause 3. The wife's duties, as outlined in Article 83, create the potential for gender injustice through psychological pressure, with Article 83 Paragraph 2 indicating a double burden in managing household affairs. Finally, Article 84 Paragraph 1 highlights the potential for gender injustice in judging the wife as nusyuz (defiant), creating inequality in response to acts of defiance from both parties. Research implications – In the Compilation of Islamic Law, marriage aims to achieve a household life that is sakinah, mawaddah, and rahmah (peaceful, loving, and affectionate). To achieve this goal, married couples must commit to fulfilling their rights and obligations according to their respective abilities. Originality/value – This research is important to identify and explain the differences in status between husbands and wives, opening up space for reflection and a better understanding of aspects of gender equality in the context of Islamic marriage.